2018
DOI: 10.1111/1750-3841.14188
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Phage Therapy into WPI Dip Coatings for Applications on Fresh Whole and Cut Fruit and Vegetable Surfaces

Abstract: The practical application is to prevent bacterial cross contamination of fresh produce by using a combination of edible coating with bacteriophages. The results demonstrate enhanced loading and stability of phages on fresh produce when used in combination with an edible coating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 45 publications
2
21
0
1
Order By: Relevance
“…More recently, studies have reported phages encapsulation to be further applied in food products. For instance, the incorporation of phages targeting E. coli strains into matrices such as whey protein isolate (WPI) coatings/films (Huang & Nitin, 2019;Tomat et al, 2019;Vonasek, Choi, Sanchez, & Nitin, 2018) or chitosan (Amarillas et al, 2018) has proved to reduce the loss of phage activity during storage and to be a highly effective to prevent bacterial contamination of vegetable surfaces, meat, fish feed and tomatoes. A cocktail of phages targeting Salmonella has also been microencapsulated in WPI coatings and exhibited a high efficiency against Salmonella serovars, but it was less efficient when applied on fresh foods (Petsong, Benjakul, & Vongkamjan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies have reported phages encapsulation to be further applied in food products. For instance, the incorporation of phages targeting E. coli strains into matrices such as whey protein isolate (WPI) coatings/films (Huang & Nitin, 2019;Tomat et al, 2019;Vonasek, Choi, Sanchez, & Nitin, 2018) or chitosan (Amarillas et al, 2018) has proved to reduce the loss of phage activity during storage and to be a highly effective to prevent bacterial contamination of vegetable surfaces, meat, fish feed and tomatoes. A cocktail of phages targeting Salmonella has also been microencapsulated in WPI coatings and exhibited a high efficiency against Salmonella serovars, but it was less efficient when applied on fresh foods (Petsong, Benjakul, & Vongkamjan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Phage immobilisation techniques have several generalisable downstream applications in biomedicine and food production. For example, phage coating of catheters efficiently prevents Staphylococcus epidermitis biofilm formation [ 39 ] and prevents Pseudomonas aeruginosa in wound dressing [ 40 ], and phage coating of food packing materials has been applied to prevent food from spoiling [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whey protein isolate provides an excellent barrier to oxygen and light, thus reducing these oxidative stresses 65 . WPI also protects the viral head of bacteriophages from desiccation, thus slowing bacteriophages of infectivity 35,66 . Our results were also similar to those seen for bacteriophages in electrospun PVP fibers 67,68 .…”
Section: Discussionmentioning
confidence: 99%